2004
DOI: 10.1016/j.jacc.2003.09.070
|View full text |Cite
|
Sign up to set email alerts
|

Hospital percutaneous coronary intervention volume and patient mortality, 1998 to 2000

Abstract: We found no evidence of higher in-hospital mortality in patients undergoing PCI at medium-volume hospitals compared with patients treated at hospitals with annual PCI volumes of 400 cases of more, suggesting current ACC/AHA PCI hospital volume minimums may merit reevaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 44 publications
1
77
0
1
Order By: Relevance
“…Further, there is only a weak relationship with unplanned CABG [38][39][40][41][42][43][44], which is likely due to the many clinical variables that impact outcomes (Table III). In the Northern New England Registry [26] there was no relationship between operator volume and clinical success, MI as a complication, mortality (low or high-risk patients) or in-hospital CABG.…”
Section: Public Reporting Of Pci Volumementioning
confidence: 99%
See 1 more Smart Citation
“…Further, there is only a weak relationship with unplanned CABG [38][39][40][41][42][43][44], which is likely due to the many clinical variables that impact outcomes (Table III). In the Northern New England Registry [26] there was no relationship between operator volume and clinical success, MI as a complication, mortality (low or high-risk patients) or in-hospital CABG.…”
Section: Public Reporting Of Pci Volumementioning
confidence: 99%
“…Institutional volume may be a better quality indicator, but it does not supersede validated clinical outcomes [29,33,37,38,49]. A team with more experience in high-risk cases, increased sharing techniques, greater collaboration with surgical colleagues, and broader access to newer technologies are possible explanations for better outcomes at large-volume institutions.…”
Section: Public Reporting Of Pci Volumementioning
confidence: 99%
“…[14][15][16][17][18][19] However, in the earlier reports on hospital numbers, the minimum number of all PCIs needed to guarantee an acceptable mortality was 160 to 200 per year per hospital. 14,15 In another registry on 446 hospitals in the US, PCI had a lower mortality than thrombolysis as a treatment for acute myocardial infarction when performed in a hospital with a case load of 17 or more. 16 Only recently Hannan reported on the New York PCI reporting system.…”
Section: -12mentioning
confidence: 99%
“…Previous studies also have demonstrated above suggestions in many surgical procedures, such as coronary artery bypass graft, pancreatic and thoracic surgery (1)(2)(3). In cardiology, the relationship between hospital percutaneous coronary intervention (PCI) volume and in-hospital mortality has been widely investigated (4,5). There is some evidence that the disparity in outcomes of PCI between high-and low-volume hospitals has narrowed over time (6).…”
Section: Introductionmentioning
confidence: 93%